An Implementation of Expilicit Instruction Strategy in Teaching Recount Text on the Students Writing Skill - Musdizal Musdizal; Mira Oktavianus; Dairabi Kamil (Departement of Mathematics Education, 2022)
In English learning, there are four skills that need to be mastered by English students, they are listening, speaking, reading and writing. As four skills writing is one of the most important skill for students. Writing becomes one of the most important aspect of the language skills because the students are helped to expand the other language skill through the teaching of writing skill by teacher. The purpose of this research was to find out whether any significant effects of using Explicit Strategy in teaching recount text on students writing skill at the first grade of SMPN 26 Kerinci. The population of this research was the first grade of SMPN 26 Kerinci, there were 28 students from two classes. The sample used totaling sampling. Based on the result of this research, there is significant effect Explicit Strategy in teaching recount text on students writing skill at the first grade of SMPN 26 Kerinci. Therefore, the researcher suggested for English teacher to use Explicit Instruction Strategy in teaching writing, especially in teaching of writing recount text.